Risk of Urinary Bladder Cancer in Patients With Inflammatory Bowel Diseases: A Meta-Analysis - Geng, Zhihua; Geng, Qing (Frontiers in Surgery, 2021)
A systematic search of the PubMed, Cochrane, Embase, and Web of Science databases was conducted to investigate the risk of urinary bladder cancer (BC) in patients with inflammatory bowel disease (IBD). We identified 168 articles, of which 11 met the inclusion and exclusion criteria. Our analysis included 165,176 patients with IBD, 491 of whom had BC. Overall, the pooled standardized incidence ratio (SIR) was 0.99 (95% CI: 0.87–1.12; I2 = 0%). Further subgroup analysis showed that BC risk was neither statistically higher for Crohn's disease (CD) (SIR: 1.19; 95% CI: 0.94–1.44; I2 = 0%) nor for patients with ulcerative colitis (UC) (SIR: 0.92; 95% CI: 0.77–1.06; I2 = 0%). In the analysis of two case-control studies providing data on BC in UC and CD combined, IBD patients seemed to have a higher risk of BC than non-IBD patients (relative risk: 1.25; 95% CI: 0.77–2.03; I2 = 37.5%). Although the overall risk of BC was not significantly increased among patients with IBD, there was a weak trend for the risk to be elevated in CD patients, indicating marginal significance. These findings may primarily be explained by the opposite effects of smoking on CD and UC as well as the immunosuppressive drugs these patients often take.